A new family of poecilostomatoid copepods (Strepidae fam. nov.) associated with the sun coral, Tubastraea coccinea Lesson, 1829 in Taiwan - Cheng, Yu-Rong; Liu, Shang-Yin Vanson; Dai, Chang-Feng (Zootaxa, 2016)
Both sexes of Strepus elongatus gen. et sp. nov. are described based on specimens obtained from the coral host, Tubastraea coccinea Lesson, 1829, collected from shallow water reefs in Taiwan. The new species belongs to a new family of the copepod order Poecilostomatoida and displays the following morphological characteristics: (1) poecilostome type of well developed piercing mandibles, (2) absence of an oral cone, (3) highly transformed body, (4) 4-segmented antennules, (5) 2-segmented maxilliped, (6) caudal rami with only two setae, and (7) complete loss of legs 1–5 in the female, but legs 1–2 being represented by a free segment bearing two terminal setae in the male. In addition, the phylogenetic analysis based on 18S ribosomal RNA sequence data showed that S. elongatus clustered with a Sabelliphilus–Anchimolgus clade (Sabelliphilidae + Xarifiidae + Rhynchomolgidae + Anchimolgidae), and that the average genetic distance between S. elongatus gen. et sp. nov. and representatives of the six most closely related families (0.064) was higher than the average distances among those families (0.028). Therefore, based on both morphological and molecular data, a new family Strepidae fam. nov. is proposed to accommodate its only known species, S. elongatus gen. et sp. nov.